PENGARUH KONSUMSI KUKIS ’MANGPIS’ TERHADAP PEMERIKSAAN GULA DARAH PERIVER DAN VENA SUBJEK OBESITAS - Nawai, Fatmayanti; Syauqy, Ahmad; Pramono, Adriyan; Afifah, Diana Nur; Noer, Etika Ratna (Persagi, 2023)
Dietary fiber, resistant starch, bioactive compounds, phenolic antioxidants, flavonoids, and inulin are found in mangrove and banana flour. The combination of the two flours is expected to produce cookies that increase the metabolism of obesity. This study aims to identify the chemical characteristics, level of preference, and glycemic index of mangrove and banana flour cookies (mangpis) to increase metabolism in obese subjects. This study consists of three stages. The first stage of chemical characteristic analysis and preference level using a Completely Randomized Design (CRD) design with 4 treatments with 2 repetitions. The second stage of the best and selected formula from the level of preference tests its glycemic index value and glycemic load using a Completely Randomized Design. and the third stage of steamed intervention using Pre-Post Randomized Control Group Design. The results showed that F1 had the highest air, dietary fiber, crude fiber, and resistant starch content, while F0 had the highest protein, energy, and carbohydrate content. F2 cookies had the highest fat content. The glycemic index of steamed F2 was included in the medium category with a low glycemic load. The 28-day F2 intervention reduced triglycerides but did not affect fasting blood sugar or insulin levels.